Analisa dan perancangan Knowledge Management System pada SMA Negeri Ragunan Jakarta Selatan - Sita Anggraeni; Sunarti Sunarti; Jenie Sundari (Journal of Applied Informatics and Computing, 2018)
As one of the public high schools intended for student athletes and sportsmen in the Ragunan area of ​​South Jakarta, Ragunan State Senior High Schools not only want to improve their students 'sports achievements but want to improve their students' academic performance. This research proposes to the need for a Knowledge Management System. The Knowledge Management concept tries to combine two major strengths namely Knowledge and Management by managing all the resources (resources) that are in the company so that it is easy to store, recover, and distributed to the right people quickly according to needs. By designing a web-based knowledge management system at Ragunan State High School, it becomes one of the learning media and information related specifically between teachers and students. The website is one of the media in many ways in delivering information, through education websites, the teachers and students can exchange information and even conduct learning activities. System development in this study using prototype methods, with this method of development and users can interact with each other during the system manufacturing process. this application can be applied to support the dissemination of information and dissemination of the existence of schools and to make effective the implementation of educational activities between teachers and students even without face to face.